Discovery of high antibacterial and antitumor effects against multi-drug resistant clinically isolated bacteria and MCF-7 and AGS cell lines by biosynthesized silver nanoparticles using Oxalis corniculata extract - Ebrahimzadeh, Mohammad Ali; Alizadeh, Seyedeh Roya; Hashemi, Zahra (European Journal of Chemistry, 2023)
The green technique is a unique way to produce functional nanoparticles. We examined the green synthesis of Ag nanoparticles (O-AgNPs) by the extract of Oxalis corniculata. Green-synthesized O-AgNPs were accomplished by monitoring critical factors such as concentration, pH, reaction time, and temperature. Several analytical techniques, including scanning electron microscopy, energy-dispersive X-ray spectroscopy, X-ray diffraction analysis, and UV-Vis spectroscopy, were applied to characterize O-AgNPs. The SEM analysis showed O-AgNPs with a spherical shape and an average size of 33.57 nm. The XRD pattern indicated the face-centered cubic (fcc) structure of the prepared O-AgNPs. The anticancer activity of the synthesized O-AgNPs was investigated in MCF-7 (breast) and AGS (gastric) cell lines, indicating high anticancer effects against selected cell lines. The growth of all selected bacteria containing Gram+ and Gram- was inhibited by O-AgNPs. O-AgNPs showed greater inhibition in comparison to conventional antibiotics. As a result, our green synthesized AgNPs using plant extracts exhibited anticancer and antibacterial activities.